2012
DOI: 10.1111/j.1467-9485.2011.00576.x
|View full text |Cite
|
Sign up to set email alerts
|

The Shape of the Income Distribution and Economic Growth – Evidence from Swedish Labor Market Regions

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…This technique is extensively used in panel-data growth studies to allow for unobserved panel heterogeneity and simultaneously control for endogeneity bias arising from the possibility that one or more of the explanatory variables in growth regressions may not be strictly exogenous (see e.g. Aisen and Veiga, 2013;Bond et al, 2001;Christiansen et al, 2013;Guariglia and Poncet, 2008;Hoeffler, 2002;Rooth and Stenberg, 2012;Saidi and Aloui, 2010;Yamarik, 2010). Indeed, a common feature of most empirical growth models is that causation between the dependent and the right-hand-side variables may run in both directions, leading to endogeneity bias.…”
Section: Description Of the Data And Estimation Resultsmentioning
confidence: 99%
“…This technique is extensively used in panel-data growth studies to allow for unobserved panel heterogeneity and simultaneously control for endogeneity bias arising from the possibility that one or more of the explanatory variables in growth regressions may not be strictly exogenous (see e.g. Aisen and Veiga, 2013;Bond et al, 2001;Christiansen et al, 2013;Guariglia and Poncet, 2008;Hoeffler, 2002;Rooth and Stenberg, 2012;Saidi and Aloui, 2010;Yamarik, 2010). Indeed, a common feature of most empirical growth models is that causation between the dependent and the right-hand-side variables may run in both directions, leading to endogeneity bias.…”
Section: Description Of the Data And Estimation Resultsmentioning
confidence: 99%
“…Because of heterogeneity in cross country data, some studies emphasize on subnational data in inequality and growth nexus (Kennedy et al, 2017;De Dominicis et al, 2008;Naguib, 2015). There are several evidences that studies use sub-national data from the US (Benos and Karagiannis, 2017;Fallah and Partridge, 2007;Frank, 2009), Sweden (Rooth and Stenberg, 2012), Australia (Kennedy et al, 2017) and Turkey (Gungor, 2010). Researcher uses sub-national data used multi-year interval data, and Kennedy et al (2017) contributed in this issue, who used annual sub-national data of income inequality from Australia for the period of 1942-2013.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, it has also been observed that inequality has a positive impact on growth (Forbes, 2000;Li and Zou, 1998). More recent work has presented evidence that there is a very weak association between inequality and growth (Rooth and Stenberg, 2012). That is, income inequality is considered to be one of the determinants of efficiency improvement, capital accumulation, and technological progress.…”
Section: Datamentioning
confidence: 99%